Effective Single Drug Treatment of Lymphatic Filariasis through Enhanced Transdermal Delivery of Ivermectin Liposomes using Solid and Dissolving Microneedles - Devineni, Jyothirmayee; Pravallika, Ch.Durga; Rani, Boothapati Sudha; Nalluri, Buchi Naidu (Indian Journal of Pharmaceutical Education and Research, 2020)
Objectives: The present investigation was to study the combination of liposomes (LP) and microneedles (MNs) as a single drug treatment approach for the delivery of an antifilarial drug, ivermectin (IVM) in which the role of MN arrays (commercial solid MNs of different lengths and laboratory fabricated polymeric dissolving MNs of length 0.6mm) in increasing the in vitro permeation of IVM-LP across pig ear skin was studied. Experimental: IVMLP was formulated and optimized using solvent injection method and thin layer film hydration method. The optimized IVM-LP formulation F4 were then incorporated into the dissolving MN arrays and tested for the increased permeation of IVM by the assistance of MNs. A transdermal patch with IVM-LP was prepared as passive permeation study. Solid MNs (poke and patch) were tested for assisting the penetration of IVM from IVMLP patch. In vitro skin permeation studies were carried out using Franz diffusion cells for a period of 24 h. Results and Discussion: The optimized IVM-LP was < 100 nm in diameter suitable for lymphatic uptake and MNs of IVM-LP had good mechanical strength, insertion capabilities. From the dermatokinetic study it was evident that the delivery of IVM into the excised porcine skin by MNs was significantly higher than that from passive studies, with apparent permeability coefficient of 0.798±0.009 cm/h for 0.6mm dissolving MNs. Conclusion: MN assisted transdermal delivery of IVM-LP could be used to target specifically human lymphatic system where single drug treatment for lymphatic filariasis could be made possible.
Keywords: Lymphatic filariasis; Ivermectin; Liposomes; Microneedles; Transdermal; drug delivery systems; Bioavailability